1999
DOI: 10.1056/nejm199908053410606
|View full text |Cite
|
Sign up to set email alerts
|

The Association between For-Profit Hospital Ownership and Increased Medicare Spending

Abstract: Both the rates of per capita Medicare spending and the increases in spending rates were greater in areas served by for-profit hospitals than in areas served by not-for-profit hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 21 publications
3
49
0
4
Order By: Relevance
“…We were able to contact 9 of the 10 authors and to confirm that 6 of these studies had no measure of variance, 3 grouped private notfor-profit and public not-for-profit hospitals together and the authors either no longer had the data or could not rerun the analyses excluding the public hospitals, and 1 study had data on charges for care and did not have data on payments for care; these 10 studies were excluded from our systematic review (Table 1). [15][16][17][18][19][20][21][22][23][24] All 10 excluded studies found higher payments or charges for care at private forprofit hospitals than at not-for-profit hospitals; in 6 of the 10, the differences were statistically significant. [15][16][17]21,22,24 Table 2 presents the study characteristics and Table 3 the study methodology of the 8 observational studies included in our systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We were able to contact 9 of the 10 authors and to confirm that 6 of these studies had no measure of variance, 3 grouped private notfor-profit and public not-for-profit hospitals together and the authors either no longer had the data or could not rerun the analyses excluding the public hospitals, and 1 study had data on charges for care and did not have data on payments for care; these 10 studies were excluded from our systematic review (Table 1). [15][16][17][18][19][20][21][22][23][24] All 10 excluded studies found higher payments or charges for care at private forprofit hospitals than at not-for-profit hospitals; in 6 of the 10, the differences were statistically significant. [15][16][17]21,22,24 Table 2 presents the study characteristics and Table 3 the study methodology of the 8 observational studies included in our systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] All 10 excluded studies found higher payments or charges for care at private forprofit hospitals than at not-for-profit hospitals; in 6 of the 10, the differences were statistically significant. [15][16][17]21,22,24 Table 2 presents the study characteristics and Table 3 the study methodology of the 8 observational studies included in our systematic review. We obtained or confirmed data with the investigators for 7 studies; the sole author of the remaining study had died.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, this waste has been estimated at $400 billion (Freeman, 2009; Contrary to Friedman's claims, for-profit health care delivery is more expensive without delivering better care. Medicare spending per capita (adjusted for health characteristics) in communities with for-profit hospitals ($5,172) was higher and increasing faster compared to communities with non-profit hospitals ($4,440) in 1995 (Silverman, et al, 1999; see also Woolhandler & Himmelstein, 1997). A study by Alan Sager and Deborah Socolar of the Boston University School of Public Health estimated that in the US "one-half of health spending goes to clinical and administrative waste, excess prices, and theft" (Sager & Socolar, 2005, p. ii).…”
Section: Friedman's Microeconomics: What's Wrongmentioning
confidence: 99%
“…There are an increasing number of studies on health care practices, financing, and organization that rely on Medicare data, including (to name but a few) research on the use of medical services (Himelhoch et al, 2004), cancer (McClish et al, 2003), hospital quality (Needleman et al, 2003), procedure rates (Escarce and McGuire, 2003), longevity and Medicare spending (Lubitz et al, 1995), hospital ownership and Medicare spending (Silverman and Skinner, 1999), health maintenance organization enrollment patterns (Morgan et al, 1997), the use of mammography (Blustein, 1995), mortality and use of services (Gornick et al, 1996), and the effects of type of hospital on the cost and quality of care (Taylor et al, 1999). These studies are of critical importance for public policy, and for the development of strategies to contain escalating health care costs, but they often rely on corrupted data.…”
mentioning
confidence: 99%